2023
DOI: 10.1038/s41597-023-01969-8
|View full text |Cite
|
Sign up to set email alerts
|

Addressing barriers in FAIR data practices for biomedical data

Abstract: AIR data sharing is integral to spur research reproducibility, promote data reuse, and accelerate research. However, the first step in using these data assets -discovering that they exist -is compounded by problems in incentives, standardization, and coordination of efforts. In 2023, the National Institutes of Health (NIH) implemented their updated Data Sharing Policy, which mandates timely data sharing of all NIH-funded data. However, for the policy to shift the data sharing culture, to improve research repro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 14 publications
(12 reference statements)
1
6
0
Order By: Relevance
“…The latter, combined with the relatively low response rate (42.7%) for this section, suggests a lack of awareness and limited implementation of FAIR principles among the surveyed database stakeholders. This is consistent with other studies that have found low levels of FAIR compliance [20]. Therefore, the results underline the importance and need for targeted interventions to promote FAIR compliance and standardize data sharing practices across different domains.…”
Section: Discussionsupporting
confidence: 91%
“…The latter, combined with the relatively low response rate (42.7%) for this section, suggests a lack of awareness and limited implementation of FAIR principles among the surveyed database stakeholders. This is consistent with other studies that have found low levels of FAIR compliance [20]. Therefore, the results underline the importance and need for targeted interventions to promote FAIR compliance and standardize data sharing practices across different domains.…”
Section: Discussionsupporting
confidence: 91%
“…The primary barriers to widely sharing and reusing data are a set of interrelated challenges (see companion Commentary on Addressing barriers in FAIR data practices for biomedical data 65 ), including: (1) lack of incentives for researchers to share information in a timely and transparent manner; (2) logistical challenges with collecting, sharing, and finding data; and (3) lack of documentation and interoperability conflicts which make it difficult to reuse data. As a result, our main goal in this work was to tackle the logistical barrier: collecting sufficient metadata that promotes easily discovering datasets, the first step in reusing public data.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding Data sharing, our study revealed a lack of adherence to FAIR data principles (2 [1-2.5]). Despite the recognized importance of FAIR data, practical application remains challenging [36][37][38]. Numerous obstacles, including ethical, organizational, legal, technical, political, and economic issues, hindered timely and effective data sharing between health authorities and stakeholders [2,19,38,39].…”
Section: Dimension Two -Operational Activitiesmentioning
confidence: 99%